Nursing students experience during the COVID-19 pandemic: a qualitative research - Farfán-Zúñiga, Ximena; Jaman-Mewes, Paula; Zimmermann-Vildoso, Melissa; Campos-Lobos, Claudia (Investigación y Educación en Enfermería, 2023)
Objective. To describe the professional practice experiences of fifth year nursing students during the COVID-19 pandemic. Methods. Qualitative research design with content analysis. Participant sampling was purposive. 13 fifth-year nursing students participated. All of them completed their professional clinical practice in public hospitals and private clinics who cared for COVID-19 patients in Chile. The data were obtained through guided online written self-reflections. Results. Three main themes were inductively identified: (1) Facing with a very difficult and stressful situation, due to the permanent use of personal protection elements, multiple emotions, and physical fatigue, as well as facing ethical-clinical dilemmas in daily tasks; (2) Recognising different coping styles in difficult moments, highlighting contact with significant people and combination form of support and harmful ways of coping with stress; and (3) Experiences disciplinary learning and personal growth, such as: nursing care management, interpersonal skills in times of crisis and having contributed to the country in this adverse context. Conclusion. The clinical experience of the students in times of COVID-19, was an opportunity to learn how to perform nursing care in times of crisis, humanize care and support health teams in some of the country's hospitals.